Cell surface photoengineering enables modeling of glycocalyx shedding dynamics. Issue 22 (23rd May 2022) - Purcell, Sean C.; Zhang, Michelle H.; Honigfort, Daniel J.; Ng, Hans Jefferson C.; Michalak, Austen L.; Godula, Kamil
Abstract : Engineering cell surfaces with light-responsive mucin mimetic glycopolymers enables modeling of mucosal glycocalyx shedding and its possible roles in mucosal epithelium protection. Abstract : The cellular glycocalyx, composed of membrane associated glycoproteins and glycolipids, is a complex and dynamic interface that facilitates interactions between cells and their environment. The glycocalyx composition is continuously changing through biosynthesis of new glycoconjugates and membrane turnover. Various glycocalyx components, such as mucins, can also be rapidly shed from the cell surface in response to acute events, such as pathogenic threat. Mucins, which are large extended glycoproteins, deliver important protective functions against infection by creating a physical barrier at the cell surface and by capturing and clearing pathogens through shedding. Evaluating these mucin functions may provide better understanding of early stages of pathogenesis; however, tools to tailor the composition and dynamics of the glycocalyx with precision are still limited. Here, we report a chemical cell surface engineering strategy to model the shedding behavior of mucins with spatial and temporal control. We generated synthetic mucin mimetic glycopolymers terminated with a photolabile membrane anchor, which could be introduced into the membranes of living cells and, subsequently, released upon exposure to UV light. By tuning the molecular density of the artificial glycocalyx we evaluated lectin crosslinking and its effect on shedding, showing that lectins can stabilize the glycocalyx and limit release of the mucin mimetics from the cell surface. Our findings indicate that endogenous and pathogen-associated lectins, which are known to interact with the host-cell glycocalyx, may alter mucin shedding dynamics and influence the protective properties of the mucosal barrier. More broadly, we present a method which enables photoengineering of the glycocalyx and can be used to facilitate the study of glycocalyx dynamics in other biological contexts.